-4(3y-9)-y=4(y-3)

Simple and best practice solution for -4(3y-9)-y=4(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3y-9)-y=4(y-3) equation:


Simplifying
-4(3y + -9) + -1y = 4(y + -3)

Reorder the terms:
-4(-9 + 3y) + -1y = 4(y + -3)
(-9 * -4 + 3y * -4) + -1y = 4(y + -3)
(36 + -12y) + -1y = 4(y + -3)

Combine like terms: -12y + -1y = -13y
36 + -13y = 4(y + -3)

Reorder the terms:
36 + -13y = 4(-3 + y)
36 + -13y = (-3 * 4 + y * 4)
36 + -13y = (-12 + 4y)

Solving
36 + -13y = -12 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
36 + -13y + -4y = -12 + 4y + -4y

Combine like terms: -13y + -4y = -17y
36 + -17y = -12 + 4y + -4y

Combine like terms: 4y + -4y = 0
36 + -17y = -12 + 0
36 + -17y = -12

Add '-36' to each side of the equation.
36 + -36 + -17y = -12 + -36

Combine like terms: 36 + -36 = 0
0 + -17y = -12 + -36
-17y = -12 + -36

Combine like terms: -12 + -36 = -48
-17y = -48

Divide each side by '-17'.
y = 2.823529412

Simplifying
y = 2.823529412

See similar equations:

| -16t^2+120t+56=0 | | -31/2x=3 | | (2x-4)/39=24/(x-6) | | y=36cos(x) | | 7(x+3)=5x+13 | | 2/3n-5/8=7/8 | | 2.4=(3m+4) | | x/2(28-x)-96=0 | | g(3)=9 | | 0.2(x+3)-0.4(x+3)=0.2x-0.6 | | m-64.5=-7.1 | | 64b^3+1=0 | | -27=-253+x | | 13(t-3)+5t=6(3t+5)-8 | | 2/3g=4/9 | | 0=x^3+3x^2-24x-30 | | 28x^2-x-2=0 | | 5x-4=8y-3 | | 5n=20(4+.25) | | x^2+32x-126=0 | | -24=.263+x | | (3+3x)(6-x)=510 | | -39=x-62 | | 3-5(2+4x)=5 | | 12x-5=5x+23 | | 2x^2-x^2+1-4=0 | | 4cos^2x-3cosx=0 | | 5(a-12)-24=3(a+2) | | 2x^3-5x-69=0 | | 1.3(x+2)+5.6=17.3 | | x-3=-.5x+3 | | 5-9x=-4x |

Equations solver categories